Leaf trait modification in European beech trees in response to climatic and edaphic drought. (1st December 2021) - Weithmann, G.; Schuldt, B.; Link, R. M.; Heil, D.; Hoeber, S.; John, H.; Müller‐Haubold, H.; Schüller, L.‐M.; Schumann, K.; Leuschner, C.
Abstract: Leaf morphological and physiological traits control the carbon and water relations of mature trees and are determinants of drought tolerance, but it is not well understood how they are modified in response to water deficits. We analysed five sun‐canopy leaf traits (mean leaf size (LS), specific leaf area (SLA), Huber value (HV), water potential at turgor loss point ( Ψ tlp ) and foliar carbon isotope signature (δ 13 C)) in European beech ( Fagus sylvatica L.) across three precipitation gradients sampled in moist (2010), dry (2019) and very dry (2018) summers, and tested their response to short‐term water deficits (climatic water balance (CWB) preceding sample collection) and long‐term water availability (mean annual precipitation (MAP), plant‐available soil water capacity (AWC) and neighbourhood competition). Across the 34 sites, LS varied seven‐fold (3.9−27.0 cm 2 ), SLA four‐fold (77.1−306.9 cm²·g −1 ) and HV six‐fold (1.0−6.65 cm 2 ·m −2 ). In the 2018 dataset, LS showed a negative and HV a positive relationship to MAP, which contradicts relations found in multi‐species samples. Average Ψ tlp ranged from −1.90 to −2.62 MPa and decreased across the sites with decreasing CWB in the month prior to measurement, as well as with decreasing MAP and AWC in 2019. Studied leaf traits varied considerably between years, suggesting that mast fruiting and the severe 2018 drought caused the formation of smaller leaves. We conclude that sun‐canopy leaf traits of European beech exhibit considerable plasticity in response to climatic and edaphic aridity, and that osmotic adjustment may be an important element in the drought response strategy of this anisohydric tree species. Abstract : Sun‐canopy leaf traits of Fagus sylvatica exhibit considerable plasticity in response to aridity, and osmotic adjustment may be an important element in the drought‐response strategy.